Differences between subclinical ruminators and reflectors in narrating autobiographical memories: innovative moments and autobiographical reasoning - Habermas, Tilmann (2021)
The datasets presented in this study can be found in online repositories. The names of the repository/repositories and accession number(s) can be found below: psycharchives, http://dx.doi.org/10.23668/psycharchives.4562.